THE EFFECT OF SERVICE QUALITY FOR CUSTOMER SATISFACTION TO CREATE SUSTAINABLE GROWING COMPANIES - David Sukardi Kodrat (Jurnal Teknobisnis, 2012)
The purpose of this study is to determine the effect of service quality on customer satisfaction to create a sustainable growth enterprise. The issue of the research is based on an interesting event in the airline industry, which experienced an increase in passengers. Yet, there is different situation in the company who sold tickets for this airline industry. Population of the study was customers of PT. Java Holiday Tour and Travel Service. Simple Random sampling method has been applied. It was obtained a sample of 240 respondents. The result showed, the value of the determination coefficient (R2) of 0.761 which means that the independent variables (tangible, reliability, responsiveness, assurance, and empathy) had significant effect of consumer satisfaction (Y) 76.1 percent. The variable quality of service attributes into customer preferences ware responsiveness (0,102), empathy (0,098), reliability (0.095), tangible (0.073) and assurance (0.063). New customers will pay more attention to tangible attributes. On the other hand, the old customer in the A segment will require a higher empathy attribute rather than customer in segment below it.